The PERAN ADMIRole of Public Administration in Addressing Market Failure: Between Regulation and Policy InnovationNISTRASI PUBLIK DALAM MENGATASI KEGAGALAN PASAR ANTARA REGULASI DAN INOVASI KEBIJAKAN - Tri Wahyuni Novianti; Tursina Megawari (Balai Diklat Keagamaan Bandung, 2026)
This study aims to analyze the role of public administration in addressing market failures in Indonesia, with a particular emphasis on balancing regulation and policy innovation. Market failure occurs when market mechanisms fail to deliver goods and services efficiently, equitably, and sustainably, as reflected in monopolies, externalities, information asymmetry, and the under-provision of public goods.This research adopts a descriptive qualitative approach based on a literature review and official government documents, focusing on regulatory dynamics and policy innovation in strategic public sectors. Data were analyzed using the Miles and Huberman interactive model, with source triangulation drawn from government reports, Statistics Indonesia (BPS), and academic publications.The findings indicate that public administration performs a dual role: as a regulator ensuring legal certainty and public protection, and as a policy innovator capable of adapting to social, economic, and technological changes. However, several structural, administrative, and social barriers persist, including weak inter-agency coordination, limited bureaucratic capacity, and societal resistance to new policies.To address these challenges, key strategies include strengthening bureaucratic capacity, promoting evidence-based policymaking, implementing adaptive public communication, and enhancing cross-sector collaboration through co-production and collaborative governance.This study contributes to the public administration literature by demonstrating that a balanced integration of regulation and policy innovation is essential for effective state intervention in market failures and for advancing inclusive and sustainable development.